2003
DOI: 10.1007/s00430-003-0180-3
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death in thymus during experimental paracoccidioidomycosis

Abstract: Many works have shown that immunosuppressive effects induced by systemic mycosis can be related to primary lymphoid organ damage. Previous studies in our laboratory showed that Paracoccidioides brasiliensis was able to invade the thymus, inducing a severe atrophy with significant reduction of cortical area along with a loss of cortico-medullary boundary. The objective of the present study was to investigate whether thymic atrophy is caused by programmed cell death (PCD) and to examine the ultrastructural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 23 publications
2
21
0
1
Order By: Relevance
“…Increased apoptotic index triggered by autophagic programmed cell death Thymus growth-stimulatory factor extracted from S. involvens, a fern Brito et al 2003;Gayathri et al 2011;MendesGiannini et al 2008;Savino 2006;Souto et al 2003 Bacteria Immune reaction to the thymic infection Borges et al 2012;Nobrega et al 2007Nobrega et al , 2010Reiley et al 2012 Francisella tularensis, F. tularensis an analogous patho-physiological model similar to HIVinfected human in terms of disease progression (Policicchio et al 2016). During infection of newborn rhesus macaques with SIV, ATI-associated events (including enhanced death and depletion of thymocytes by various apoptotic mechanisms) very similar to those described in HIV-infected humans (Rosenzweig et al 2000) are observed.…”
Section: Paracoccidioides Brasiliensismentioning
confidence: 99%
See 2 more Smart Citations
“…Increased apoptotic index triggered by autophagic programmed cell death Thymus growth-stimulatory factor extracted from S. involvens, a fern Brito et al 2003;Gayathri et al 2011;MendesGiannini et al 2008;Savino 2006;Souto et al 2003 Bacteria Immune reaction to the thymic infection Borges et al 2012;Nobrega et al 2007Nobrega et al , 2010Reiley et al 2012 Francisella tularensis, F. tularensis an analogous patho-physiological model similar to HIVinfected human in terms of disease progression (Policicchio et al 2016). During infection of newborn rhesus macaques with SIV, ATI-associated events (including enhanced death and depletion of thymocytes by various apoptotic mechanisms) very similar to those described in HIV-infected humans (Rosenzweig et al 2000) are observed.…”
Section: Paracoccidioides Brasiliensismentioning
confidence: 99%
“…This invasion was associated with severe ATI as a primary event that was characterized by a decrease in thymus weight, an increase in number of histiocytes, limited distinction of the cortico-medullary junction along with degenerative changes in the thymic cortex . Mechanistically, ATI during experimental paracoccidioidomycosis was caused by apoptosis, as indicated by a significant increase in the apoptotic index as well as typical cellular changes that were triggered by autophagic programmed cell death (Mendes-Giannini et al 2008;Souto et al 2003). Gayathri et al (2011) investigated the effect of an extract of a fern known as Selaginella involvens that was shown to have thymus growth-stimulatory properties and found that this substance protected cortisone-treated immuno-compromised mice from an infection with Aspergillus fumigatus.…”
Section: Fungal Infections and Atimentioning
confidence: 99%
See 1 more Smart Citation
“…A/J and B10.A male mice from CEMIB/UNICAMP were intraperitoneally inoculated with 5x10 6 yeasts of Pb (highly Pb18 or slight Pb265 strain) or sterile phosphate buffered saline (control). Lots of 5 mice were weighted and sacrificed at 1, 3, 5, 7 and 14 days post-infection (pi).…”
Section: Experimental Designmentioning
confidence: 99%
“…In BALB/c mice, we observed that a virulent isolate of Pb is able to invade the thymic microenvironment inducing severe atrophy, depletion of the cortical layer, loss of the corticomedullary delimitation, and medullary and subcapsular inflammatory infiltrate (1). Also, an increase in programmed cell death (PCD) by apoptosis and autophagy was observed (6). In this work, we evaluated thymic alterations induced by highly and slightly virulent isolates of Pb in susceptible (B10.A) and resistant mice (A/J).…”
Section: Introductionmentioning
confidence: 99%